The Saudi State as an Identity Racketeer - Rich, Ben; MacQueen, B. (2017)
Where substantial research has examined the Saudi state’s symbiosis with the Islamic revivalist movement commonly known as ‘Wahhabism’, little has considered how the dynamics of state formation underpin this relationship. This article argues that a continuous and circular political logic sits behind the Saudi state’s patronage of the revivalist movement since 1744. It proposes a four-stage model that explains how and why the Saudi state has maintained its support of the revivalist movement over this prolonged period. This article will first outline this model, before moving to a detailed analysis of the development of Saudi state authority to highlight the recurrent manner in which the spiritual concerns of revivalists have often been constructed by the state to counter challenges to its authority, a pattern showcased most recently during the Arab Spring and the war in Yemen. The relevance of this model persists today, and will continue to shape the decisions, policies and perceptions of the Saudi political elite for the foreseeable future.